The Urgency of Technology And Information Technology (ICT) Development in Realizing The Transformation of Advanced Nias Regency in The Era of Civil Society 5.0 and Industrial Revolution 4.0 - Ayler Beniah Ndraha; Eliyunus Waruwu; Delipiter Lase; Ofelius Laia; Darwis Robinson Manalu; Elisati Kurniawan Telaumbanua; Asokhiwa Zega (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Research This research discusses the significant impact of e-government implementation in improving efficiency of public administration and community participation in the era of digital disruption. digital disruption era. The focus is on analyzing the development and challenges of integrating information technology integration in governance to create transparent and accountable public services. transparent and accountable public services. This research aims to analyze the influence and benefits of e-government implementation in improving government efficiency, public service transparency, and participation. Government efficiency, public service transparency, and public participation in Indonesia, as well as identifying the barriers and challenges of e-government implementation. Participation in Indonesia, as well as identifying barriers and challenges faced in its implementation. in its implementation. This research uses a comprehensive literature review method method to integrate various perspectives and empirical findings. This approach includes topic exploration, collection of relevant literature, and analysis and synthesis of data to answer the research questions. In addition, SWOT analysis was used to evaluate the condition of e-government in Nias Regency and develop improvement strategies that include Nias Regency and develop improvement strategies that include strengthening strengths, utilizing opportunities, reducing weaknesses, and addressing threats. The research This research shows that the implementation of information and communication technology (ICT) in Nias Regency is still at the maturation stage, with strong local government commitment but faced with commitment but faced with challenges of geography, limited infrastructure and infrastructure, and human resource competencies. SWOT analysis identified potential development potential and opportunities, as well as threats and weaknesses that need to be addressed through collaboration with various stakeholders. through collaboration with various stakeholders. Improving ICT in Nias Regency requires an integrated strategy that includes developing infrastructure, improving human resource competencies, and collaboration with the private sector, to realize the transformation of Nias Regency towards an effective and efficient e-government. effective and efficient e-government.